Unterpolsteine und ihre Behandlung: CME : zertifizierte Fortbildung - Abd Ali, Furat; Vincze, P.; Herrmann, T. R. W.; Netsch, C.; Becker, B.; Hatiboglu, G.; Homberg, R.; Lehrich, K.; Miernik, A.; Olbert, P.; Schöb, D. S.; Herrmann, Jonas; et al. (Die Urologie, 2025)
The most frequent initial clinical symptom is flank pain, which occurs in approximately half of affected patients with stones of the upper urinary tract. Of these patients approximately half require treatment and 50% will again have new stones in the future. Only 8% of urinary stones are clinically inapparent with 25-50% of the stones located in the lower calyx group and are incidentally discovered during the diagnostics of symptomatic stones. Stones in the lower calyx are more difficult to treat than other kidney stones due to the localization and the resulting access possibilities. The treatment must therefore be planned and carried out individually according to the available treatment options. Since the development of modern flexible ureterorenoscopes (URS) retrograde stone removal, which has few complications, has been highly valued in the treatment of stones of the lower calyx due to the desired primary stone clearance rates. Limiting factors are the longer treatment times for large stone masses and the considerable material costs. Furthermore, the various forms of percutaneous nephrolitholapaxy provide additional methods for the treatment of larger lower caliceal stones.
Online publiziert: 23. Juni 2025
Gesehen am 26.08.2025